Phase II, single-arm trial of preoperative short-course radiotherapy followed by chemotherapy and camrelizumab in locally advanced rectal cancer - Jun Fan; Jing Wang; Tao Zhang; Xin Li; Lan Zhang; Zheng Wang; Tao Liu; Gang Li; Peng Zhang; Chi Ma; Ming Cai; Gang Wu; et al. (Journal for ImmunoTherapy of Cancer)
Background In locally advanced rectal cancer (LARC), preoperative short-course radiotherapy (SCRT) with delayed surgery has been shown to be as effective as long-course chemoradiotherapy, with only modest benefits. This study aimed to evaluate the efficacy and safety of preoperative SCRT combined with subsequent CAPOX (capecitabine and oxaliplatin) and the anti-PD-1 antibody camrelizumab in patients with LARC.Methods This was a prospective, single-arm, phase II trial. Treatment-naïve patients with histologically confirmed T3-4N0M0 or T1-4N+M0 rectal adenocarcinoma received 5×5 Gy SCRT with two subsequent 21-day cycles of CAPOX plus camrelizumab after 1 week, followed by radical surgery after 1 week. The primary endpoint was pathological complete response (pCR) rate. Biomarker analysis was performed to identify a potential predictor of pCR to treatment.Results From November 7, 2019 to September 14, 2020, 30 patients were enrolled, and 27 patients received at least one dose of CAPOX plus camrelizumab. Surgery was performed in 27 (100%) patients. The pCR (ypT0N0) rate was 48.1% (13/27), including 46.2% (12/26) for proficient mismatch repair (MMR) tumors and 100% (1/1) for deficient MMR tumors. Immune-related adverse events were all grade 1–2, with the most common being reactive cutaneous capillary endothelial proliferation (81.5%). No grade 4/5 adverse events occurred. Biomarker analysis showed patients without FGFR1–3 deletions had a better tendency for pCR.Conclusions SCRT combined with subsequent CAPOX plus camrelizumab followed by delayed surgery showed a favorable pCR rate with good tolerance in patients with LARC, especially in the proficient MMR setting. A randomized controlled trial is ongoing to confirm these results.Trial registration number ClinicalTrials.gov identifier: NCT04231552.